Design and Synthesis of Dihydroxamic Acids as HDAC6/8/10 Inhibitors. (13th May 2020) - Morgen, Michael; Steimbach, Raphael R.; Géraldy, Magalie; Hellweg, Lars; Sehr, Peter; Ridinger, Johannes; Witt, Olaf; Oehme, Ina; Herbst‐Gervasoni, Corey J.; Osko, Jeremy D.; Porter, Nicholas J.; Christianson, David W.; et al.
Abstract: We report the synthesis and evaluation of a class of selective multitarget agents for the inhibition of HDAC6, HDAC8, and HDAC10. The concept for this study grew out of a structural analysis of the two selective inhibitors Tubastatin A (HDAC6/10) and PCI‐34051 (HDAC8), which we recognized share the same N ‐benzylindole core. Hybridization of the two inhibitor structures resulted in dihydroxamic acids with benzyl‐indole and ‐indazole core motifs. These substances exhibit potent activity against HDAC6, HDAC8, and HDAC10, while retaining selectivity over HDAC1, HDAC2, and HDAC3. The best substance inhibited the viability of the SK‐N‐BE(2)C neuroblastoma cell line with an IC50 value similar to a combination treatment with Tubastatin A and PCI‐34051. This compound class establishes a proof of concept for such hybrid molecules and could serve as a starting point for the further development of enhanced HDAC6/8/10 inhibitors. Abstract : Best of both worlds : A new HDAC inhibitor class has been developed by hybridizing two structurally related, but functionally distinct, inhibitors: PCI‐34051 (HDAC8 inhibitor) and Tubastatin A (HDAC6/10 inhibitor). The resulting dihydroxamic acids are capable of inhibiting HDACs 6, 8, and 10, and are characterized by a benzyl‐indole/indazole scaffold, which functions as both cap and linker group.